Parent-child relationship and hope as mediators between parental support, school climate and academic self-efficacy among early adolescents in the Klang Valley, Malaysia - Wong, Annie Kai Sze (2022)
Parental support and school climate are well documented to be two significant factors in determining adolescents’ academic development Yet, there is still much to be discovered about the underlying process of such relationships especially in the Malaysian context. To address this paucity, the present study was carried out to investigate the mediation roles of the parent-child relationship (PCR) and hopeful thinking in the linkage between paternal support, maternal support, school climate, and early adolescents’ academic efficacy. Parental support included the subdomains of involvement, structure, and autonomy support. The academic efficacy has measured overall academic efficacy and STEM efficacy domains. This research was a quantitative study that has employed the correlational research design to measure the hypotheses. A total of 247 male and 247 female young adolescents (9 to 11 years old) from five public primary schools in Klang Valley, Malaysia were selected to participate in this study using stratified random sampling. The instruments used in this study were Perceptions of Parents Scales, New Jersey School Climate Survey, Security Scale, Children’s Hope Scale, Self-Efficacy Questionnaire for Children, and STEM Efficacy Children Scale (SECS). Data were collected using a self-administered questionnaire and Structural Equation Modeling (Amos) was used to test the hypothesized models with multiple mediators using the AMOS software. The current findings have suggested that mothers’ structure (β=.259 to.398, p <. 05), fathers’ involvement (β =.188 to .207, p < .05), structure supports (β =.109, p < .05), and school climate (β =.443 to .458, p < .05) were positive direct predictors of academic efficacy. Some discrepancies were found regarding the significant paths of fathers' and mothers' areas of support in cultivating academic efficacy, as well as the effect sizes of independent constructs compared to previous literature. These inconsistencies may be due to the differences in parenting and educational beliefs and norms practiced by people in different cultures and regions, which determined early adolescents' receptivity to such social messages. The PCR and hope have sequentially mediated the linkage between parental support and academic efficacy. Apart from that, the findings also showed that hope has significantly mediated the linkage between school climate and efficacy. To conclude, though the influence of parenting and school factors on early adolescents has become less or indirect, it was still important for the development of positive internal mechanisms in the formation of positive academic efficacy in them. The present findings were important in provided insightful suggestions for planning and refining academic intervention strategies used in schools and families. In addition, it helped advance Overlapping Spheres of Influence Model and Social Cognitive Theory by explaining the mediating role of PCR and hope as underlying processes that linked the contextual factors of parental support, school climate, and the development of early adolescents' academic efficacy.